Geometrical variability of the femoral distal epiphysis - S. E. Baybakov; L. V. Gorbov; T. S. Alekseenko; K. P. Chekalin (Сеченовский вестник)
In the article the principle of the classification of the anatomical shape of the object with complex geometry – distal femoral epiphysis. The approach is based on a study of the ratio of the length, width and height of the medial and lateral condyles of the object being studied. For the first time shows sexual dimorphism in the shape of distal femoral epiphysis – from women significantly more often than men, found the prevalence of the length of the medial condyle of the lateral length. It is possible that this feature may be due to changes associated with childbirth.